1996
DOI: 10.1107/s0108767396000761
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Back-Diffraction Profiles with an Si (111) Plate

Abstract: A two-and, alternatively, a four-crystal monochromator were used for simultaneous measurements of the profiles backward (h) and forward (o) diffracted by a thin Si (111) crystal plate for diffraction angles up to exactly 90 ° at DCI-LURE (Orsay). It is shown that the set-up with a four-crystal monochromator allows the characterization of the back-diffraction region for any crystal plate reflection. Asymmetry and full width at half-maximum (FWHM) of the experimental backwarddiffraction profiles are analyzed. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…However, there are very few experimental studies have been devoted to the measurements of a Bragg diffraction intensity profile at scattering angles close to 90 (see e.g. [7] and references therein). This is, probably, the reason why theoretical considerations of the 90 reflection have only been given to the reflection from a perfect crystal, see e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are very few experimental studies have been devoted to the measurements of a Bragg diffraction intensity profile at scattering angles close to 90 (see e.g. [7] and references therein). This is, probably, the reason why theoretical considerations of the 90 reflection have only been given to the reflection from a perfect crystal, see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[8], and crystal-lattice spacing changes, e.g. [7,13], make this experimental environment very attractive for use as an optical element and as an enhanced analytical technique.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the extremely high energy resolution that can be achieved [1,4] in a backscattered beam might allow one to perform highly monochromatic radiation experiments that cannot be implemented using far from 90 , Bragg reflection geometry. However, there have been only a few reported experiments that were devoted to the measurement of a diffraction intensity profile at scattering angles close to a Bragg angle of 90 (see [7] and references therein). The major experimental difficulty associated with the direct observation and quantitative measurement of this intensity profile was to achieve a significant spatial separation of the incident and backscattered beams.…”
Section: Introductionmentioning
confidence: 99%
“…This experimental difficulty is obviously due to the lack of a suitable detector system that would allow the accurate measurement of the backscattered beam intensity when it is very close to the incident beam. Recently, it was reported that the backscattered beam could be measured using an ionisation chamber [7] that also intercepted the incident beam. In this experiment the researchers observed the symmetrically reflected beams in the vicinity of the exact 90 Bragg reflection from a Si(111) crystal [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation